Tazkiyatun Nafs bi al-Thariqah al-Shufiah: Mu’assasan ‘ala Ra’yi Al-Qusyairî fi Tafsîrihi Lathâif Al-Isyârât - Wahyu Septrianto; Ussisa 'Alat Taqwa; Afifah Bidayah Syukri Zarkasyi; Mohammad Aliyan Ashadi (Studia Quranika, 2021)
Nowadays, human utilize their intelligence, power, and wealth only for the satisfaction for the lust. They disobey to Allah’s commands. Moreover, they are easy to blame one another and behave badly. Accordingly, a few people in this era are destroyed morally and mentally. It is necessary for scholars' interpretation to give answers to the problems. Tafsîr Lathâif Al-Isyârât one of sollution to answer this problem. Researcher employs Al-Qusyairî statements because of his Sufism. Sufism is considered crucial because Sufism is the most relevant science to purify the soul. In addition, the explanation of sufi interpretation is different from other interpreters in studying this theme. This research uses descriptive methods and analysis in explaining the interpretation of Al-Qusyairi in purifying the soul. The research shows that there are several stages to purify our hearts, and our souls. they are tawâdhu' in all behaviors and senses (avoiding pride), paying debts on time, keeping the sanctity of the mind of the soul and body from sin, forgiving anyone, staying away from the principles by doing anything in place, worship without hope, obey whatever God's destiny, remembering death and the last day, strive sincerely in work, and finally asking for proof of what written in the Qur'an. Those are assumed able to purify our souls and our hearts.